The Catalytic Mechanism of β -Lactamases: NMR Titration of an Active-Site Lysine Residue of the TEM-1 Enzyme - Damblon, Christian; Raquet, Xavier; Lian, Lu-Yun; Lamotte-Brasseur, Josette; Fonze, Eveline; Charlier, Paulette; Gordon C. K. Roberts; Frère, Jean-Marie (Proceedings of the National Academy of Sciences - PNAS, 1996)
β -Lactamases are widespread in the bacterial world, where they are responsible for resistance to penicillins, cephalosporins, and related compounds, currently the most widely used antibacterial agents. Detailed structural and mechanistic understanding of these enzymes can be expected to guide the design of new antibacterial compounds resistant to their action. A number of high-resolution structures are available for class A β -lactamases, whose catalytic mechanism involves the acylation of a serine residue at the active site. The identity of the general base which participates in the activation of this serine residue during catalysis has been the subject of controversy, both a lysine residue and a glutamic acid residue having been proposed as candidates for this role. We have used the pH dependence of chemical modification of ε -amino groups by 2,4,6-trinitrobenzenesulfonate and the pH dependence of the ε -methylene 1H and 13C chemical shifts (in enzyme selectively labeled with [ε -13C]lysine) to estimate the pKa of the relevant lysine residue, lysine-73, of TEM-1 β -lactamase. Both methods show that the pKa of this residue is > 10, making it very unlikely that this residue could act as a proton acceptor in catalysis. An alternative mechanism in which this role is performed by glutamate-166 through an intervening water molecule is described.